Local low‐frequency vibration accelerates healing of full‐thickness wounds in a hyperglycemic rat model - Daijiro Haba; Qi Qin; Chihiro Takizawa; Sanai Tomida; Takeo Minematsu; Hiromi Sanada; Gojiro Nakagami (Journal of Diabetes Investigation, 2023)
Abstract Aims/Introduction Local low‐frequency vibration (LLFV) promotes vasodilation and blood flow, enhancing wound healing in diabetic foot ulcers with angiopathy. However, vibration‐induced vasodilation does not occur, owing to chronic hyperglycemia and inflammation. We hypothesized that LLFV improves glycometabolism and inflammation, leading to vasodilation and angiogenesis in diabetic wounds. Therefore, this study investigated the effect of LLFV on wound healing in hyperglycemic rats, primarily focusing on glycometabolism, inflammation, vasodilation, and angiogenesis. Materials and Methods Streptozotocin‐induced hyperglycemic Sprague–Dawley rats were used in this study. We applied LLFV to experimentally‐induced wounds at 50 Hz and 0, 600, 1,000 or 1,500 mVpp for 40 min/day from post‐wounding days (PWD) 1–14. Results The relative wound areas in the 600 and 1,000 mVpp groups on PWD 5–7 were significantly smaller than those at 0 mVpp. The expression of Glo‐1 (1,500 mVpp) and Slc2A4 (1,000 and 1,500 mVpp) was upregulated on PWD 4 and 14, respectively. However, there was no difference in methylglyoxal expression levels in any group until PWD 14. At 1,000 mVpp, the expression of Tnfa on PWD 4, and that of Ptx3 and Ccl2 on PWD 14 was downregulated. Furthermore, the M1/M2 macrophage ratio was considerably decreased on both days. The expression of Nos3, Vegfa and vascular endothelial growth factor A was upregulated on PWD 4. In addition, vasodilation and angiogenesis were more obvious on PWD 14 with 1,000 mVpp. Conclusions The results suggest that LLFV promotes wound healing, improves glycometabolism and inflammation, and enhances vasodilation and angiogenesis in hyperglycemic wounds.